2008
DOI: 10.1074/jbc.m800256200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ions Are Involved in the Unusual Red Shift of the Light-harvesting 1 Qy Transition of the Core Complex in Thermophilic Purple Sulfur Bacterium Thermochromatium tepidum

Abstract: Thermophilic purple sulfur bacterium, Thermochromatium tepidum, can grow at temperatures up to 58 degrees C and exhibits an unusual Qy absorption at 915 nm for the core light-harvesting complex (LH1), an approximately 35-nm red shift from those of its mesophilic counterparts. We demonstrate in this study, using a highly purified LH1-reaction center complex, that the LH1 Qy transition is strongly dependent on metal cations and Ca2+ is involved in the unusual red shift. Removal of the Ca2+ resulted in formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
123
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(136 citation statements)
references
References 49 publications
13
123
0
Order By: Relevance
“…tepidum that also exhibits a redshifted Q y absorption maximum at 915 nm (Madigan 2003). The formation of a Ca 2+ -binding site in this region of the polypeptide is thought to be responsible for the absorption shift in this bacterium (Kimura et al 2008). Although pufA 1 and pufA 2 of strain 970 display this deletion as well, the Q y redshift cannot be attributed solely to this region, because the same sequence pattern was also determined for the two Trv.…”
Section: Structure Of the Puf Operons In Strain 970 And Trv Winogradmentioning
confidence: 89%
“…tepidum that also exhibits a redshifted Q y absorption maximum at 915 nm (Madigan 2003). The formation of a Ca 2+ -binding site in this region of the polypeptide is thought to be responsible for the absorption shift in this bacterium (Kimura et al 2008). Although pufA 1 and pufA 2 of strain 970 display this deletion as well, the Q y redshift cannot be attributed solely to this region, because the same sequence pattern was also determined for the two Trv.…”
Section: Structure Of the Puf Operons In Strain 970 And Trv Winogradmentioning
confidence: 89%
“…Wang (&) Faculty of Science, Ibaraki University, Mito 310-8512, Japan e-mail: wang@mx.ibaraki.ac.jp occur in a stoichiometric ratio of Ca 2? /ab-subunit = 1:1 and the binding constant was in 10 5 M -1 order of magnitude (Kimura et al 2008). Despite the high affinity, conformational changes of the LH1 complex upon Ca 2?…”
Section: Introductionmentioning
confidence: 93%
“…In a series of investigations on the Tch. tepidum LH1 complex (Wang et al 2003;Suzuki et al 2007;Kimura et al 2008;2009), we found that the LH1 is highly stable at room temperature when copurified with reaction center (RC) in a LH1-RC complex form, and calcium ions are involved in both the enhanced thermal stability and the large red shift of the LH1 Q y transition. Removal of the Ca 2?…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, the LH1 αTrp43 was proposed to be located near the putative binding site for BChl molecule [19]. Dissimilar to the purple non-sulfur bacteria, calcium ions were demonstrated to be involved in the unusual red shift of the LH1 Q y transition of the core complex in Thermochromatium tepidum [20]. Hydrogen bonds were intensively studied in the binding of BChl molecules to RC [21].…”
Section: Introductionmentioning
confidence: 99%